2012
DOI: 10.1089/gtmb.2011.0268
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy Between Initial High Expression of Interest in Clinical Cancer Genetic Testing and Actual Low Uptake in an Asian Population

Abstract: A significant discrepancy exists between an initial high interest in testing and actual low uptake. Health programs that address cost issues and education to correct misperceptions may improve genetic information utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…Unfortunately, our FDR predictive testing rate of 6% in our service is disappointing, far below the reported ratios in other established services 23. The low uptake of predictive testing is contrary to survey findings of high interest in predictive screening of unaffected family members in Singapore 3 7 25. Patients who declined predictive testing in other studies have cited fear of emotional burden and stress associated with genetic information on themselves as reasons for not availing themselves to genetic testing 3 7 26.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Unfortunately, our FDR predictive testing rate of 6% in our service is disappointing, far below the reported ratios in other established services 23. The low uptake of predictive testing is contrary to survey findings of high interest in predictive screening of unaffected family members in Singapore 3 7 25. Patients who declined predictive testing in other studies have cited fear of emotional burden and stress associated with genetic information on themselves as reasons for not availing themselves to genetic testing 3 7 26.…”
Section: Discussioncontrasting
confidence: 64%
“…The low uptake of predictive testing is contrary to survey findings of high interest in predictive screening of unaffected family members in Singapore 3 7 25. Patients who declined predictive testing in other studies have cited fear of emotional burden and stress associated with genetic information on themselves as reasons for not availing themselves to genetic testing 3 7 26. This is an area in critical need for further research so as to best understand how we can improve FDR testing rates to optimise health impact.…”
Section: Discussionmentioning
confidence: 92%
“…We designed an open‐ended, semistructured interview guide to explore key areas, based on our previous clinical experiences and a literature review . The draft interview guide was pilot‐tested on colleagues and 1 volunteer patient not participating in the study.…”
Section: Methodsmentioning
confidence: 99%
“…We designed an open-ended, semistructured interview guide to explore key areas, based on our previous clinical experiences and a literature review. [13][14][15] The draft interview guide was pilot-tested on colleagues and 1 volunteer patient not participating in the study. Following the pilot, the research team consisting of clinicians, health services researchers, sociologists, and an educator added expertise and knowledge of local health literacy and education among patients to refine the final question guide and probes ( Table S1).…”
Section: Data Collectionmentioning
confidence: 99%
“…In this regard, Malm et al [ 37 ] reported that circulating monocyte numbers and percentages robustly increase up to 7 days following a muscle-damaging eccentric protocol; an effect which paralleled the appearance of macrophages in skeletal muscle tissue. While we are unaware of studies that have examined the ability of BCAA supplementation to reduce post-exercise monocyte proliferation and skeletal muscle macrophage infiltration, it has been recently posited that BCAAs can be transaminated to glutamate in order to increase glutamine synthesis which, in turn, can be consumed by macrophages as a fuel source to propagate inflammation [ 38 ]. Notwithstanding, our findings that BCAAs are able to prevent the elevation in monocyte percentages over three days of rigorous weightlifting may suggest that BCAAs may possess an anti-inflammatory properties and should be further researched.…”
Section: Discussionmentioning
confidence: 99%